Enhancing Agrobacterium-mediated plant transformation efficiency through improved ternary vector systems and auxotrophic strains - Aliu, Ephraim; Ji, Qing; Wlazlo, Anna; Grosic, Sehiza; Azanu, Mercy K.; Wang, Kan; Lee, Keunsub (Frontiers in Plant Science, 2024)
Agrobacterium-mediated transformation is an essential tool for functional genomics studies and crop improvements. Recently developed ternary vector systems, which consist of a T-DNA vector and a compatible virulence (vir) gene helper plasmid (ternary helper), demonstrated that including an additional vir gene helper plasmid into disarmed Agrobacterium strains significantly improves T-DNA delivery efficiency, enhancing plant transformation. Here, we report the development of a new ternary helper and thymidine auxotrophic Agrobacterium strains to boost Agrobacterium-mediated plant transformation efficiency. Auxotrophic Agrobacterium strains are useful in reducing Agrobacterium overgrowth after the co-cultivation period because they can be easily removed from the explants due to their dependence on essential nutrient supplementation. We generated thymidine auxotrophic strains from public Agrobacterium strains EHA101, EHA105, EHA105D, and LBA4404. These strains exhibited thymidine-dependent growth in the bacterial medium, and transient GUS expression assay using Arabidopsis seedlings showed that they retain similar T-DNA transfer capability as their original strains. Auxotrophic strains EHA105Thy- and LBA4404T1 were tested for maize B104 immature embryo transformation using our rapid transformation method, and both strains demonstrated comparable transformation frequencies to the control strain LBA4404Thy-. In addition, our new ternary helper pKL2299A, which carries the virA gene from pTiBo542 in addition to other vir gene operons (virG, virB, virC, virD, virE, and virJ), demonstrated consistently improved maize B104 immature embryo transformation frequencies compared to the original version of pKL2299 (33.3% vs 25.6%, respectively). Therefore, our improved Agrobacterium system, including auxotrophic disarmed Agrobacterium strains and a new ternary helper plasmid, can be useful for enhancing plant transformation and genome editing applications.